The development and research tradition of statistical quality control. (2nd December 2009) - Hossain, Muhammad Muazzem; Prybutok, Victor R.; Abdullah, A.B.M.; Talukder, Majharul
The purpose of this study is to fill three gaps in the literature of quality control. First, this study expounds the chronological development of statistical quality control (SQC) to date, for there is a paucity of an up-to-date chronology of SQC in the literature. Second, the concept of statistical quality control has been analysed from the perspective of scientific inquiry to determine whether SQC has evolved or has been evolving as an evolutionary, revolutionary or progressive research program. Third, this paper discusses whether the discipline of statistical quality control has its own research tradition. We employed a qualitative method to address our research questions. We argue that the concept of statistical quality control has emerged as a scientific revolution in the arena of quality control and that the discipline of statistical quality control has its own research tradition. This study provides both practitioners and academicians with not only an up-to-date account of SQC but a sense of the legitimacy of SQC as a discipline. SQC provides a system's perspective to quality control and has paved the way for enterprise-wide quality philosophies such as TQC, TQM, zero defects, Six Sigma, ISO, etc.